KUITANSI SEBAGAI DOKUMEN PEMBUKTIAN JUAL BELI TANAH - Chien Rosley Tuapetel; I Dewa Ayu Widyani; Haposan Sahala Raja Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Land sale and purchase must be done in front of a PPAT and proven by a Sale and Purchase Deed (AJB) to provide legal certainty. However, the practice of buying and selling land under the hands with receipts is still common because the process is simpler even though it is legally risky. The formulation of the problem in this thesis is whether the proof of sale and purchase of land based on receipts can be said to be valid according to the law and whether the Judge’s consideration in deciding Case No. 217/Pdt.G/2022/PN PBR is in accordance with applicable legal provisions. This research is a normative legal research with a case approach. The data used is secondary data in the form of primary legal materials: Civil Code, Law Number 5 of 1960 on Basic Agrarian Principles, Government Regulation Number 24 of 1997 on Land Registration, Government Regulation Number 34 of 1998 on the Regulation of the Position of Land Deed Officials and Supreme Court Circular Letter (SEMA) Number 4 of 2016 on the Enforcement of the Formulation of the Results of the 2016 Plenary Meeting of the Supreme Court Chamber, while primary legal materials are obtained from books, journals and so on, tertiary legal materials in the form of dictionaries and internet searches, then the collected legal materials are compiled and analysed. From the results of this research, it can be concluded that the sale and purchase of land with receipts can be considered valid according to the law in several circumstances, in accordance with Article 37 Paragraph (2) of Government Regulation No. 24 of 1997 concerning Land Registration. In addition, the judge’s decision in the case of Pekanbaru District Court Decision Number 217/Pdt.G/2022/PN Pbr was correct. Although the land sale and purchase transaction between the Plaintiff (Dian Haryani) and the Defendant (Dewi Bungsu) was conducted under the hand and did not involve a Land Deed Official (PPAT), the judge considered the good faith of the Plaintiff who had paid off the land price.